Technological Knowledge (TK) of Elementary School Teacher Education Program Students in Elementary Science Learning - Trivena Trivena; Hakpantria Hakpantria; Reni Lolotandung (Universitas Muhammadiyah Enrekang, 2022)
Teaching is a component of the success of education. Technological knowledge (TK) or technological knowledge, which is one of the frameworks of technological pedagogical content knowledge (TPACK), is knowledge that students possess in order to be able to transmit or impart content to facilitate understanding for students. The aim of this study was to identify the kindergarten students of prospective primary school teachers in elementary science learning. This study uses a descriptive type of research with a quantitative approach. The research population are the students of the UKI Toraja Elementary School Teacher Education Class of 2019. While the research sample consists of students who have taken the courses Introduction to School Fields, Science Learning Development, and Computer Applications, there are no less than 72 respondents. The instrument used is an instrument developed from the research of Akyuz, Desstya, and Mishra, tested for validity and reliability and specially designed for the elementary school level. Data processing is done using the Microsoft Excel application, where the collected data is then searched for the average score per indicator and category. The results of the study showed that the average overall TK of the primary school teacher candidates in elementary science instruction was 7,3. From these results, it can be concluded that the kindergarten teacher candidates for primary school are classified as